(untitled) (Journal of Digital Learning Futures p-ISSN 3117-6054 and e-ISSN 3117-6062, 2025)
The digital revolution is transforming educational systems globally, shifting from traditional classroom instruction to AI-powered personalized learning. This paper explores how artificial intelligence enables individualized learning pathways, real-time feedback, and adaptive content delivery that improves student engagement and learning outcomes. Unlike traditional classrooms, where instructions are uniform for all learners, AI systems adjust the pace, difficulty, and teaching style according to student performance and behavioral patterns. This research examines pedagogical transitions, evaluates engagement metrics across learning environments, and highlights challenges involving data privacy, teacher training, and digital equity. Based on institutional case studies and student engagement data, the study concludes that AI-powered personalization significantly enhances academic performance, motivation, and self-regulated learning—making education more inclusive and learner-centric